2013
DOI: 10.1098/rspb.2012.2517
|View full text |Cite
|
Sign up to set email alerts
|

Song type matching is an honest early threat signal in a hierarchical animal communication system

Abstract: Aggressive encounters between animals often involve significant amounts of signalling before or in lieu of physical fights. When, as is often the case, these apparent threat signals are neither inherently costly nor inherently indicative of fighting ability, we should ask whether they are in fact honest signals, i.e. do they predict that escalation is imminent? While signalling theories have indicated that such 'conventional' threat signals can honestly predict escalation, attempts to gather supporting empiric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
112
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 102 publications
(116 citation statements)
references
References 35 publications
4
112
0
Order By: Relevance
“…'type matched'). Of these four signalling measures, the first two have been shown to reliably predict attack during simulated intrusions with a mount [22,27]. Type matching also has been shown to predict attack, but only in the context of a gradual escalation and not when the simulated intrusion starts from the territory centre [27].…”
Section: (C) Response Measuresmentioning
confidence: 99%
See 4 more Smart Citations
“…'type matched'). Of these four signalling measures, the first two have been shown to reliably predict attack during simulated intrusions with a mount [22,27]. Type matching also has been shown to predict attack, but only in the context of a gradual escalation and not when the simulated intrusion starts from the territory centre [27].…”
Section: (C) Response Measuresmentioning
confidence: 99%
“…Although these studies have found that some putative threat signals are indeed correlated with concurrent or subsequent aggressive behaviour, the relationship between signalling levels and actual aggression is far from perfect. For example, in our recent study on song sparrows (Melospiza melodia), we found that while the level of low amplitude ('soft') songs on average reliably predicted whether or not a song sparrow would attack a taxidermic mount later in the trial, a substantial number of birds that signalled at a high level did not attack, whereas others that signalled at a low level (or not at all) did attack [27], see also [22]. Soft songs and wing waves were able to correctly predict only 66.7% and 62.3%, respectively [27]-significantly different from chance, but far from perfect.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations